Culture-positive unilateral panophthalmitis in a serology-positive case of dengue hemorrhagic fever - Richa Kamal; Dhaivat Shah; Satish Sharma; Madharuvasal Krishnan Janani; Arindam Kar; Kumar Saurabh; Rupak Roy; Hajib Narahari Rao Madhavan (Indian Journal of Ophthalmology, 2018)
Dengue fever, a mosquito-borne disease commonly found in the tropics, is one of the most prevalent forms of Flavivirus infection in humans. Symptomatically, it is characterized by fever, arthralgia, headache, and rash. Ophthalmic manifestations can involve both the anterior and posterior segment. Panophthalmitis is rare in dengue hemorrhagic fever, and there is no report of culture-positive panophthalmitis in this setting. Here, we report a case of a serology-positive 33-year-old male patient of dengue hemorrhagic fever who developed sudden onset pain, redness, and proptosis in the right eye. The patient subsequently developed panophthalmitis in his right eye, and Bacillus cereus was isolated from eviscerated sample. This case provides unique insights into pathogenesis of panophthalmitis in dengue and highlights the management options.